(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
After the independence of our country, special importance began to be attached to the issue of raising the younger generation, giving it Knowledge, which is its future. For this reason, as early as the first days of independence, the restoration of our spirituality, to the level of world templates and requirements based on its further upgrade, harmonization with modern requirements particular importance is attached to the release.